Absorption characteristics of solvents for carbon dioxide capture - Sholeh Ma' mun; Hallvard Svendsen; Olav Julissen (Jurnal Rekayasa Proses, 2007)
This study focuses on the absorption characteristics of solvents for CO2 capture. The objective is to develop new and more efficient solvents or solvent mixtures with higher absorption rates and loading capacities than existing ones. CO2 absorption was investigated at 40°C using both alkanolamine-based and non-alkanolamine-based solvents. The absorption characteristics, crucial for CO2 removal, depend on the absorption rate and capacity of the solvents. All absorbents are compared to the commercially used MEA. Experimental results reveal that most tested absorbents exhibit poorer performance than MEA. However, a 30-wt% AEEA in aqueous solution emerges as a potential contender, demonstrating superior absorption characteristics. In comparison to 30-wt% MEA, the 30-wt%- AEEA shows a higher absorption rate from a loading of 0.35 and increased absorption capacity (0.82 mol CO2/mol AEEA and 0.47 mol CO2/mol MEA at 9.5 kPa CO2 partial pressure).